Negros Oriental in the Context of the Philippine Revolution - Cleope, Earl Jude Paul L. (Silliman Journal, 2022)
AS THE NATION commemorated the centennial of the Philippine Revolution this year, many projects and activities were undertaken in order to make this event truly momentous and rele-vant. It is noteworthy to mention, that as we Filipinos try to remi-nisce and understand the deeds and actions of our ancestors in this important period of our nation, we should also endeavor to examine the history of our locality and its contributions to the making of our national history. In particular, there is a need to examine the discourses surrounding the Philippine Revolution and locate them in their regional, provincial, and local contexts so that th torical significance, specifically to the province of Negros Oriental, can be understood . This present study proceeds from this critical framework.